UPAYA GURU DALAM MENINGKATKAN KECERDASAN SPIRITUAL SISWA PADA MATA PELAJARAN PAI (Studi kasus pada SMK Muara Indonesia) - Ramadhan, Dhamir Rozan; Yasin, Hadi (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
At this time, there is an increasing moral crisis in education experienced in Indonesia which started from the weak instillation of polite values ​​to early childhood, especially spiritual instillation of children. So here is the importance of instilling spiritual intelligence by taking a religious education approach based on the Qur'an. This study aims to determine the efforts of teachers in improving the spiritual intelligence of their students at SMK Muara Indonesia and to find out how the picture of the spiritual intelligence of their students is so that later what is done at SMK Muara Indonesia can be emulated by other schools in terms of improving spiritual intelligence.This study uses a qualitative research method with a descriptive approach, using data sources through observation and interviews with related informants including the principal, PAI teacher and vice principal, BK teacher and representatives of 2 students from SMK Muara Indonesia. The results of this study obtained that: 1) the teacher's efforts in improving spiritual intelligence are tadarus programs, congregational dhikr, sunnah prayers, congregational zuhur prayers, reading almatsurat, spiritual guidance, 2) these efforts can be concluded as successful because most students show changes and improvements in attitudes, behavior, and habits for worship although there are still a small number of students who have not shown any improvement. The difference with previous studies is that this study focuses more on programs created by schools.